The effects of normobaric and hyperbaric oxygenation on MRI signal intensities in T1-weighted, T2-weighted and FLAIR images in human brain - Velej Vida; Cankar Ksenija; Vidmar Jernej (Radiology and Oncology, 2023)
Dissolved oxygen has known paramagnetic effects in magnetic resonance imaging (MRI). The aim of this study was to compare the effects of normobaric oxygenation (NBO) and hyperbaric oxygenation (HBO) on human brain MRI signal intensities.